Bibliometric-based visualization analysis of hotspots and trends in falls research among older hospitalized patients (2013–2023) - Dong, Yang; Liu, Dandan; Yu, Ya; Xiong, Ziyu; Rao, Hongying (Frontiers in Medicine, 2025)
Purpose: Our study utilized CiteSpace 6.2 R4 to analyze a decade's worth of literature on falls among elderly hospitalized patients, from 2013 to 2023, to identify trends and provide a reference for future research and clinical guidance in fall prevention and management. Methods: We conducted a precise literature search in the Web of Science database, focusing on articles with keywords "older hospitalized patients" and "fall." The search was limited to the specified time frame to capture the most current trends. We excluded non-research articles and non-English documents, ensuring the scientific rigor of the study. After a quality assessment, 321 articles were included for visualization and analysis using CiteSpace. Results: The analysis revealed that the U.S. and China were major contributors to the field, with Harvard University and Imagama leading in publications. The research trends indicate a future focus on epidemiology, aging, and health-related topics, with the strongest citation bursts pointing towards these areas. Conclusion: This study offers a comprehensive overview of research trends in fall prevention among elderly hospitalized patients. There has been a notable increase in research attention over the past decade, with key focal points being fall risk assessment, prevention strategies, rehabilitation, and associated costs. The study also highlights the enduring interests in epidemiology, aging dynamics, and health outcomes post-2018, emphasizing the need for continued scholarly focus in these areas.